Performance of a routing and wavelength assignment scheme for an optical‐carrier‐reusable ring network. Issue 4 (1st December 2014) - Keri, Masafumi; Kitsuwan, Nattapong; Matsuura, Motoharu; Oki, Eiji
Abstract : This study investigates a heuristic routing and wavelength assignment (RWA) scheme for an optical‐carrier‐reusable ring network. This network has two unique features. First, only one light source, called the multi‐carrier light source, is required which eases the difficulty of controlling many light source devices. Second, optical carriers are reused in order to improve the efficiency of wavelength usage. Given the target of wavelength‐resource‐efficient channel establishment, performance of the heuristic RWA scheme is evaluated. To realise efficient wavelength usage, the authors formulate the RWA problem as an integer linear programming (ILP) problem of obtaining the minimum number of required wavelengths for given requests. With the ILP approach, the calculation process is not tractable in practical time. The heuristic RWA scheme introduced in this study solves the RWA problem. This scheme consists of two algorithms. Channel routes are obtained by the routing algorithm, and the wavelength assignment algorithm is then performed to assign a wavelength to each route. Moreover, two candidates, considering the shortest path and considering the avoidance of wavelength conversion, for the routing algorithm are examined. Numerical results show that the first candidate is more suitable in terms of reducing the number of required wavelengths than the second candidate.